Statistical analysis of metal chelating activity of Centella asiatica and Erythroxylum cuneatum using response surface methodology - Mohd Salim, Roshan Jahn; Adenan, Mohd Ilham; Amid, Azura; Jauri, M. H.; Sued, A.S. (Hindawi Publishing Corporation, 2013)
The purpose of the study is to evaluate the relationship between the extraction parameters and the metal chelating activity of Centella asiatica (CA) and Erythroxylum cuneatum (EC).The response surface methodology was used to optimize the extraction parameters of methanolic extract of CA and EC with respect to the metal chelating activity. For CA, Run 17 gave optimum chelating activity with IC50 = 0.93mg/mL at an extraction temperature of 25∘C, speed of agitation at 200 rpm, ratio of plant material to solvent at 1 g : 45mL and extraction time at 1.5 hour. As for EC, Run 13 with 60∘C, 200 rpm, 1 g : 35mL and 1 hour had metal chelating activity at IC50 = 0.3817mg/mL. Both optimized extracts were further partitioned using a solvent systemto evaluate the fraction responsible for the chelating activity of the plants.The hexane fraction of CA showed potential activity with chelating activity at IC50 = 0.090 and the ethyl acetate fraction of EC had IC50 = 0.120 mg/mL. The study showed that the response surface methodology helped to reduce the extraction time, temperature and agitation and subsequently improve the chelating activity of the plants in comparison to the conventional method.